Skin Resident γδ T Cell Function and Regulation in Wound Repair - Munoz, Luis D. (Int J Mol Sci, 2020)
The skin is a critical barrier that protects against damage and infection. Within the epidermis and dermis reside γδ T cells that play a variety of key roles in wound healing and tissue homeostasis. Skin-resident γδ T cells require T cell receptor (TCR) ligation, costimulation, and cytokine reception to mediate keratinocyte activity and inflammatory responses at the wound site for proper wound repair. While both epidermal and dermal γδ T cells regulate inflammatory responses in wound healing, the timing and factors produced are distinct. In the absence of growth factors, cytokines, and chemokines produced by γδ T cells, wound repair is negatively impacted. This disruption in γδ T cell function is apparent in metabolic diseases such as obesity and type 2 diabetes. This review provides the current state of knowledge on skin γδ T cell activation, regulation, and function in skin homeostasis and repair in mice and humans. As we uncover more about the complex roles played by γδ T cells in wound healing, novel targets can be discovered for future clinical therapies.